Peran Pustakawan Dalam Meningkatkan Motivasi Minat Baca Siswa Di SMA Negeri 1 Ciwidey - Saroya, Salsa; Rosiana Nurwa Indah; Rifqi Zaeni Achmad Syam (Program Studi Ilmu Perpustakaan dan Informasi, Universitas Islam Nusantara, 2023)
This research is motivated by the role of librarians in increasing students' reading interest motivation at SMA Negeri 1 Ciwidey. The purpose of this study is to determine the procurement of collections, extend service hours, tutoring and spatial arrangements available in the library in motivating students' reading interest and knowing the role of librarians in motivating students' reading interest. The theory used in this study is Abraham Maslow's Theory of Motivation. This theory suggests that basically all humans have basic needs. Self-actualization needs cognitive needs knowing, understanding, and exploring, aesthetic needs of harmony, order, and beauty. The conclusion of this study is that the role of librarians in increasing students' reading interest motivation at SMA Negeri 1 Ciwidey. With the role of librarians in procuring collections, it is certainly very useful for students and teachers who often visit the library. In addition, the extension of service hours will greatly assist students in borrowing or returning books. With tutoring, it really helps students in getting information, motivation in reading. As well as the influence of library spatial arrangements greatly affect users and librarians. In addition, the role of librarians is very important to help students in motivating students' reading interest. Keyword: librarian role, motivation, reading interest, SMA Negeri 1 Ciwidey ABSTRAK Penelitian ini dilatarbelakangi oleh peran pustakawan dalam meningkatkan motivasi minat membaca siswa di SMA Negeri 1 Ciwidey. Tujuan dari penelitian ini adalah untuk mengetahui pengadaan koleksi, perpanjangan jam layanan, bimbingan belajar dan penataan ruang yang tersedia di perpustakaan dalam memotivasi minat baca siswa dan mengetahui peran pustakawan dalam memotivasi minat membaca siswa. Teori yang digunakan dalam penelitian ini adalah Teori Motivasi Abraham Maslow. Teori ini mengemukakan bahwa pada dasarnya semua manusia mempunyai kebutuhan dasar. Aktualisasi diri membutuhkan kebutuhan kognitif mengetahui, memahami, dan mengeksplorasi, kebutuhan estetis akan keselarasan, keteraturan, dan keindahan. Kesimpulan penelitian ini adalah peran pustakawan dalam meningkatkan motivasi minat membaca siswa di SMA Negeri 1 Ciwidey. Dengan adanya peran pustakawan dalam pengadaan koleksi tentunya sangat bermanfaat bagi siswa dan guru yang sering berkunjung ke perpustakaan. Selain itu, perpanjangan jam layanan akan sangat membantu mahasiswa dalam peminjaman atau pengembalian buku. Dengan adanya bimbingan belajar sangat membantu siswa dalam mendapatkan informasi, motivasi dalam membaca. Serta pengaruh penataan ruang perpustakaan sangat mempengaruhi pengguna dan pustakawan. Selain itu peran pustakawan sangat penting untuk membantu siswa dalam memotivasi minat membaca siswa.